Maybelle in the Soup - Speck, Katie; Ratz de Tagyos, Paul (New York : Henry Holt, 2007)
When Mr. and Mrs. Peabody invite a guest to dinner, Maybelle the cockroach, who lives under their refrigerator, ignores the warnings of Henry the flea to be sensible and ends up "splashing" into a big adventure.
Keywords: Cockroaches -- Fiction; Insects -- Fiction; Curiosity -- Fiction